RE teachers’ ways of balancing children’s existential concerns and the curriculum: mirrored through established RE approaches - Osbeck, C; Lilja, A; Fancourt, N (Springer, 2025)
The relationship between learner and curriculum is foundational in education. In this study the purpose is to investigate how Swedish middle-school RE teachers balance children’s existential concerns and the curriculum content in their teaching, as well as how they describe current curricular goals and pupils’ questions, and to explore how these ways of balancing positions can be understood in light of how well-known RE approaches balance the child and the curriculum. In the analysis of the interview transcripts of the eleven middle-school teachers focussing on what the teachers express as important goals for RE, the findings were placed on a continuum between a focus on the child’s experiences and on the curriculum. The result also shows that the teachers recurrently describe pupils’ concerns and questions as relatively absent. The responses vary between “questions are lacking” and “questions are present”, with a middle position of “some interactionally created questions are present”. The child and the curriculum can never in practice be separated since they are integrated in the learning individual: in education, a particular individual is learning something specific. However, revisiting these approaches in combination with concrete examples of teachers’ experiences has brought our understanding further, and has also drawn attention to the need for awareness concerning the varying character of this relationship, as a tension, one between whose poles the teaching constantly moves or as one that falls apart in two different poles that do not necessarily need to be seen in the light of each other.